Nutritional status and motor development in children aged 0 to 5 years of Kankuama indigenous ethnicity Relación entre el estado nutricional y desarrollo motor en niños de 0 a 5 años de la etnia indígena Kankuama - Bustos León, Gina M.; Retamal-Matus, Héctor F.; Amador Rodero, Eulalia; Ramos Lengua, Shirly; Coronel Chona, Eva; Martínez Fragozo, Viviana; Albor Barraza, Carolay (My University, 2018)
Objective. To determine the relation between the motor development and the nutritional state in children of 0 to 5 years of the Kankuamo ethnic group. Materials and methods. Investigation of quantitative approach with design of analytical cross-sectional type, the population was constituted by 135 children of 0 5 children of the Kankuama ethnic group from who a no probabilistic sample by deliberate selection was obtained that fulfilled the inclusion criteria and exclusion, For the evaluation The anthropometric evaluation of the motor development was used to develop the state of the art. Results and Discussion: the collected data of the study corresponded to 135 children of the Kankuama ethnic group of who 54% corresponded to the feminine and 60% to the masculine, the ages oscillated between the 49 and 71 months with a 29.6%, in the results of a EAD the population is in the middle with a 45.2%, followed by the average group with a 27.4%, thirdly the alert group with 25.2% and single to 2.2% are in stop, as far as the nutritional state 16.3 % is in severe acute undernourishment, the 31.9 in moderate acute undernourishment, the 21.5 in acute undernourishment and a 14.1% in overweight. Conclusion. Relation between the nutritional state exists and the motor development of the children of 0 to 5 years of the Kankuama ethnic group, the statistical tests were positive for strong association, this is related to different factors between which the Kankuamo town has had cultural changes and has adopted a globalized style of life more due to the process of violence that it had to suffer, also adds the lack of education on the importance of foods, supplements and medicines to him that the boy must consume.
Keywords: child; ethnic groups; infant development; infant malnutrition; physical therapy